Morphology, Physico-Chemical Properties and Classification of Soils of Coastal Plain Sands in Owerri, Imo State, Southeastern Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Assessment of soil health and fertility depends on the understanding of properties and classifications of soils. In this study, soils from Obinze, Avu, Irete, and Amakohia were examined for morphology, physical, chemical properties, and classification. Target sampling technique was used and two profiles each dug across the four study sites. A total of 37 soil samples were collected according to horizon differentiation, and analyzed in the laboratory using standard procedures. Results showed that soils were well drained, colour matrix varied from brown (2.5 YR 3/2) to red (2.5 YR 5/8), sand dominated the fine earth materials (> 600 g/kg) with clay content (109 – 308 g/kg) irregularly distributed due to eluviation. Textural classes ranged from sandy loam to sandy clay loam, bulk density ranged from 1.0 – 1.77 Mg/cm3 with high values recorded in Amakohia. Silt/clay ratio indicated advanced weathering (< 1.0), while moisture retention capacity was low. Soil pH was moderately acidic (5.22 – 6.16), and organic carbon, nitrogen, and phosphorus levels were generally low and irregularly distributed. Exchangeable cations and cation exchange capacity varied irregularly down horizons, with low base saturation indicating low soil fertility. Soils were classified using USDA Soil Taxonomy and correlated with World Reference Base for Soil Resources. Obinze, Avu, and Amakohia soils were classified as Grossarenic Kandiudult, while Irete was Typic Kandiudult, and translates to Dystric Nitisols (World Reference Base). It is recommended that; the incorporation of crop residues and addition of organic manures will improve the properties of the soils for sustainable crop production.
Keywords: Classification; Coastal Plain Sands; Dystric Nitisols; Soil properties; Survey